Development and evaluation of a multiplexed mass spectrometry based assay for measuring candidate peptide biomarkers in Alzheimer's Disease Neuroimaging Initiative (ADNI) CSF. Issue 7 (24th April 2015) - Spellman, Daniel S.; Wildsmith, Kristin R.; Honigberg, Lee A.; Tuefferd, Marianne; Baker, David; Raghavan, Nandini; Nairn, Angus C.; Croteau, Pascal; Schirm, Michael; Allard, Rene; Lamontagne, Julie; Chelsky, Daniel; et al.
<x xml:space="preserve">Abstract</x> Purpose We describe the outcome of the Biomarkers Consortium CSF Proteomics Project (where CSF is cerebral spinal fluid), a public–private partnership of government, academia, nonprofit, and industry. The goal of this study was to evaluate a multiplexed MS‐based approach for the qualification of candidate Alzheimer's disease (AD) biomarkers using CSF samples from the AD Neuroimaging Initiative. Experimental design Reproducibility of sample processing, analytic variability, and ability to detect a variety of analytes of interest were thoroughly investigated. Multiple approaches to statistical analyses assessed whether panel analytes were associated with baseline pathology (mild cognitive impairment (MCI), AD) versus healthy controls or associated with progression for MCI patients, and included (i) univariate association analyses, (ii) univariate prediction models, (iii) exploratory multivariate analyses, and (iv) supervised multivariate analysis. Results A robust targeted MS‐based approach for the qualification of candidate AD biomarkers was developed. The results identified several peptides with potential diagnostic or predictive utility, with the most significant differences observed for the following peptides for differentiating (including peptides from hemoglobin A, hemoglobin B, and superoxide dismutase) or predicting (including peptides from neuronal pentraxin‐2, neurosecretory protein VGF (VGF), and secretogranin‐2) progression versus nonprogression from MCI to AD. Conclusions and clinical relevance These data provide potential insights into the biology of CSF in AD and MCI progression and provide a novel tool for AD researchers and clinicians working to improve diagnostic accuracy, evaluation of treatment efficacy, and early diagnosis.